Impacts of agricultural activities on the water quality of Serin River and the application of water quality analysis simulation program (WASP) - Kho, Chui Ping (Universiti Malaysia Sarawak, (UNIMAS), 2013)
In Sarawak, studies concerning small rivers are rather limited. Serin River, a drinking water source and also supplies water for life and irrigation but was polluted by agricultural activities. This study presented the pollutant concentrations in the river and application of Water Quality Analysis Simulation Program (WASP) model to understand the impacts of agricultural activities on the river; Six stations along the stretch of Serin River and the tributaries were selected for this purpose. The water samples were monitored for 14 parameters from September 2009 to September 2010. Generally, the water quality of the tributaries was poorer than the stations along the river. Water quality was the worst at the pig farm effiuent receiving tributary with the lowest mean DO (3.37 mglL) , the highest mean BODs (12.50 mglL), Cu (39.9 JlglL) and Fe (379.4 JlglL) levels and high mean Nand P concentrations. The tributary nearby a crop farm showed the highest Cd (3.7 JlglL) and Cr (85.2 JlgIL) levels and high mean BODs, N, P and Fe values. The aquaculture tributary showed the highest mean Chl-a (28.59 mglm3) and Zn (119.0 Jlg/L) concentrations, and high BODs and Fe levels. Meanwhile, the downstream station of Serin River showed the highest TSS (18.46 mgIL) and Pb (61.4 Jlg/L) concentrations and high P contents. The WASP model was calibrated and validated. At least 75% of the results of simulated variables of the segments fall in the maximum and minimum range of the field observations. If the fish farm wastewater was discharged, the simulation results showed that the DO and BODs of the rivers would have been in Class IV and V while the NH3-N predictions would have been in Class III. Moreover, the pig farm effluent simulation indicated that DO, BODs and NH3-N of receiving river would have been in Class III and IV, the N03-N exceeded Class II value and the P04-P violated the USEP A recommended value. Load reductions were proposed to improve the water quality of the receiving river to Class II of NWQS.